Effect of Ambient Temperature on Performance of Grid-Connected Inverter Installed in Thailand - Kamonpan Chumpolrat; Vichit Sangsuwan; Nuttakarn Udomdachanut; Songkiate Kittisontirak; Sasiwimon Songtrai; Perawut Chinnavornrungsee; Amornrat Limmanee; Jaran Sritharathikhun; Kobsak Sriprapha (International Journal of Photoenergy)
The effects of temperature on performance of a grid-connected inverter, and also on a photovoltaic (PV) system installed in Thailand have been investigated. It was found that the maximum efficiency of the inverter showed 2.5% drop when ambient temperature was above 37°C. The inverter performed efficiently in November and December, the months of high irradiance, and monthly average ambient temperature of lower than 35°C, allowing relatively high system performance ratio in this period. Our results show that high temperature provides negative impacts not only on the PV modules, but also on the performance of the inverter. Thus, the effect of temperature on the inverter efficiency should be taken into account when predicting energy yield or analyzing losses of the PV systems—especially in high temperature regions.